Kepentingan Negara-Negara Arab (Uni Emirat Arab, Bahrain, Sudan dan Maroko) Melakukan Normalisasi Hubungan dengan Israel - Yulia Rimapradesi; Ahmad Sahide (Mandala: Jurnal Ilmu Hubungan Internasional, 2021)
Arab states and Israel has for decades had dividing wall for diplomatic relations. The existence of ideological differences between Islam and Judaism as well as a long history of colonialism and conflict makes it difficult to unravel the conflict between of them. However, this seems to change, towards the end of 2020 with the encouragement of Donald Trump as president of the United States. Arab countries seem to forgot the events of the past and break up the wall that previously served as a barrier between them and Israel. The United Arab Emirates, Bahrain, Sudan and Morocco has reasons what they thinks are rationality that their initial stance in favor of Palestinian independence seems to be waning. This paper discuss about the interests of the Arab states in the the normalization of their relationship with Israel. The research method in this paper is qualitative method with inductive analysis with the latest data from various document sources as material for analysis. This paper concludes the interests of the United Arab Emirates, Bahrain, Sudan and Morocco are dominated by security and the economy for their countries.